IMPLEMENTASI PROGRAM KELUARGA HARAPAN DALAM UPAYA MENGENTASKAN KEMISKINAN DI KOTA BATU - Sasmito, Cahyo; Nawangsari, Ertien Rining (JPSI (Journal of Public Sector Innovations), 2019)
This research was conducted from February to April 2018 with qualitative descriptive methods. The data sources consist of: primary data sources and secondary data sources, primary data sources obtained from observations, and interviews. Interview with informants (purposive sampling) based on the interview guides as instruments, and the researchers as research instruments. While secondary data is obtained from documentation. Data analysis used the Miles and Huberman models of Sugiyono, 2017 whose activities include: data reduction, data display and conclution drawing / verification. The results of this study, the implementation of the Keluarga Harapan Program (PKH) effort to alleviate poverty in the Social Service Office of Batu City has been going well. Communication is established well with PKH Facilitators, and PKH Participants. The Social Service involves the Facilitators in meetings coordination, as provisions for improving professionals seminars and matrices in to help the Facilitators to assist PKH Participants in providing counseling to tell the terms and conditions that must be fulfilled by the Participants. The Government's Social Service of Batu City has exercised its authority both from aspects: communication, resources, disposition, and bureaucratic structure with PKH Assistants in the implementation to alleviate the PKH Participants' poverty. Therefore the implementation is being well because of the determined terms and conditions in education terms (permanent school participants) and in the health terms (long term health insurance), so that social assistance through PKH cash can be received by the Participants through the BNI account of each PKM Participant. Furthermore, the PKH Assistants help the Participants to counseling provide to PKH Participants in skills possessed develop by the each Participant. Therefore, for the long term PKH implementation in poverty alleviation efforts will be able to be realized by the Government's Social Service of Batu City.